Analisis Yuridis Terhadap Sengketa Tanah Adat dalam Perspektif Hukum Agraria Nasional - Uwais Umar; Toriqul Hadi; Ahmad Hanafi (Legal Note, 2025)
Customary land disputes are a legal phenomenon that frequently occurs in various regions of Indonesia and pose a serious challenge to the enforcement of national agrarian law. These conflicts typically arise due to overlaps between land ownership based on customary law and the recognition of land rights under positive law. This study aims to juridically analyze the root causes of customary land disputes and the efforts to resolve them within the framework of national agrarian law. The research method used is a normative juridical approach by examining the Basic Agrarian Law (UUPA), its implementing regulations, and relevant court decisions. The results of the study indicate that the weak harmonization between the customary legal system and the national legal system often leads to legal uncertainty for indigenous communities. Although the UUPA has recognized the existence of communal (ulayat) rights, its implementation in practice remains suboptimal due to the lack of technical regulations and the indecisiveness of law enforcement officials. Therefore, a more inclusive land policy reform and the strengthening of agrarian legal institutions are necessary to ensure fair protection and legal certainty for indigenous peoples.